Visualisasi Danau Sentani sebagai Inspirasi Desain Rias Fantasi Body Painting dalam Penciptaan Karya Artistik - Alissa Traf; Trisnani Widowati; Novia Restu Windayani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Indonesia has natural and cultural riches that have great potential as a source of inspiration in creating works of art, including in the field of fantasy make-up. However, the utilization of local natural potential, especially from the Papua region such as Lake Sentani, is still not optimal in developing body painting works. This research aims to determine the feasibility of visualizing Lake Sentani as inspiration for fantasy body painting make-up designs in creating artistic works. The method used is quantitative descriptive involving three expert validators in the field of beauty and design. The data collection technique is carried out through performance tests using a Likert scale assessment instrument which has been tested for validity and reliability. Assessment indicators include the visual aesthetics of works, elements and principles of fine art, the body as a medium for aesthetic expression, beauty product creativity, meaning and visual representation, and aesthetics in the field of beauty. Data analysis uses descriptive percentage techniques. The research results show that all indicators received a very feasible category with an average value of 96%. The beauty product creativity indicator received the highest score of 100%, while the other indicators were in the range 92%–97%. These findings show that the visualization of Lake Sentani can be processed into fantasy make-up works that are aesthetic, innovative and have strong visual meaning. Thus, the visualization of Lake Sentani is worthy of being used as a source of inspiration in developing fantasy body painting works based on local wisdom.